Numerical Modeling on Homogeneous Charge Compression Ignition Combustion Engine Fueled by Diesel-Ethanol Blends - H., Hanafi; M. M., Noor; K., Kadirgama; D., Ramasamy (EDP Sciences, 2015, 2016)
This paper investigates the performance and emission characteristics of HCCI engines fueled with oxygenated fuels (ethanol blend). A modeling study was conducted to investigate the impact of ethanol addition on the performance, combustion and emission characteristics of a Homogeneous Charge Compression Ignition (HCCI) engine fueled by diesel. One dimensional simulation was conducted using the renowned commercial software for diesel and its blend fuels with 5% (E5) and 10% ethanol (E10) (in vol.) under full load condition at variable engine speed ranging from 1000 to 2750 rpm with 250 rpm increment. The model was then validated with other researcher’s experimental result. Model consists of intake and exhaust systems, cylinder, head, valves and port geometries. Performance tests were conducted for volumetric efficiency, brake engine torque, brake power, brake mean effective pressure, brake specific fuel consumption, and brake thermal efficiency, while exhaust emissions were analyzed for carbon monoxide (CO) and unburned hydrocarbons (HC. The results showed that blending diesel with ethanol increases the volumetric efficiency, brake specific fuel consumption and brake thermal efficiency, while it decreases brake engine torque, brake power and brake mean effective pressure. In term of emission characteristics, the CO emissions concentrations in the engine exhaust decrease significantly with ethanol as additive. But for HC emission, its concentration increase when apply in high engine speed. In conclusion, using Ethanol as fuel additive blend with Diesel operating in HCCI shows a good result in term of performance and emission in low speed but not recommended to use in high speed engine. Ethanol-diesel blends need to researched more to make it commercially useable.